2016
DOI: 10.2298/abs151104073s
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Bacillus spp. from compost material, compost and mushroom casing soil active against Trichoderma spp.

Abstract: The isolation of bacteria was carried out from samples of straw and chicken manure, compost at various stages of the composting process and casing soil used for growing button mushrooms. A preliminary screening of 108 bacterial isolates for antagonistic activity against Trichoderma aggressivum f. europaeum showed that 23 tested isolates inhibited mycelial growth of the pathogenic fungus. Further screening with four indicator isolates of fungi revealed that all 23 bacterial isolates inhibited the growth of T. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Developing new biocontrol agents for mushroom crops is a challenge for the mushroom industry and the scientific community. Since it is notable that frequently in vitro results do not translate into efficiency in the crop, the preliminary (2018) selection of the most effective candidates appears to be an essential condition to success on crop trials (Stanojevi c et al, 2016;Aslani et al, 2018). There are also significant challenges associated with the translation of results from in vitro to in vivo due to the limited knowledge about the ecology of the mushroom crop and the difficulties of reproducing a reliable microcosm in the lab.…”
Section: Biocontrol Agents For Control Of Mushroom Parasitesmentioning
confidence: 99%
“…Developing new biocontrol agents for mushroom crops is a challenge for the mushroom industry and the scientific community. Since it is notable that frequently in vitro results do not translate into efficiency in the crop, the preliminary (2018) selection of the most effective candidates appears to be an essential condition to success on crop trials (Stanojevi c et al, 2016;Aslani et al, 2018). There are also significant challenges associated with the translation of results from in vitro to in vivo due to the limited knowledge about the ecology of the mushroom crop and the difficulties of reproducing a reliable microcosm in the lab.…”
Section: Biocontrol Agents For Control Of Mushroom Parasitesmentioning
confidence: 99%
“…To achieve the goal of improving disease control, the use of microbial-based pesticides has been considered as a rational and safe alternative to chemical control . Many recent studies have focused on the use of microbial inoculants for biological control, utilizing their ability to antagonize the pathogen by multiple modes of action (Rekanović et al, 2007;Živković et al, 2010;Saha et al, 2012;Berić et al, 2012;Solanki et al, 2013;Dimkić et al, 2013;Gupta & Vakhlu, 2015;Stanojević et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that microbial inoculants with antagonistic properties towards pathogens of agricultural crops have the potential to replace chemical pesticides which can be harmful to the environment and human health (Solanki et al, 2015). As reported before (Walker et al 1998, Yoshida et al, 2001Stanojević et al, 2016), the technique of dual culture on agar plates has proved to be an efficient and easy way to select antagonistic bacteria from a random group of bacterial isolates based on their ability to inhibit fungal growth. Several previous studies had shown that Bacillus spp.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies had shown that Bacillus spp. recovered from mushroom compost exhibited strong activity against causal agents of green mould of A. bisporus, such as T. aggressivum f. europaeum, T. harzianum, T. koningii and T. atroviride (Stanojević et al, 2016, Milijašević-Marčić et al, 2017. Additionally, Kim et al (2008) tested 20 Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%